The cult of Glykon as a 'New Religious Movement' - Sarefield, Daniel (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This essay explores the integration of eastern religions into the Roman world during the early Empire by examining one particularly successful example, the Cult of Glykon, which became popular during the later second century and following. Drawing on the characteristics that social scientists have identified as most significant in contributing to the success of New Religious Movements (NRMs) in the recent past, the presence of these features in the Cult of Glykon is considered from the surviving evidence, including the satire Alexander or the False Prophet, which was written by Lucian of Samosata. As this discussion makes clear, the Cult of Glykon appears to have achieved some measure of success as a New Religious Movement in the Roman world because it possessed many of the same characteristics. They are, therefore, a useful starting point for exploring the integration of other religious groups in the Roman world.